GC-MS Analysis and Study of the Antimicrobial Activity of Citrus paradisi, Citrus aurantifolia, and Citrus sinensis Peel Essential Oils as Hand Sanitizer - Isra Osman Mohammed; Ayat Ahmed Alrasheid; Saad Mohammed Hussein Ayoub (International Journal of Microbiology)
In the setting of healthcare, the use of hand sanitizers and antiseptics for hand hygiene is of paramount importance to avoid transfer of pathogenic microorganism through hand and skin contact. There is an increasing interest in the incorporation of essential oils in hand sanitizer’s formula to avoid the adverse effect of conventional hand sanitizers on health. This study aimed to detect the chemical constituents of citrus peel essential oils and study their antimicrobial activity compared with commercial hand sanitizers. The qualitative and quantitative analysis of the hydrodistillated essential oils of peels of grapefruit (Citrus paradisi), lime (Citrus aurantifolia), and orange (Citrus sinensis) were carried out using gas chromatography mass spectroscopy. The disc diffusion method was used to screen the antibacterial activity of the essential oils against Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Staphylococcus aureus, and Candida albicans compared with a 78% alcohol-based commercial hand sanitizer. The antimicrobial testing results were statistically analyzed. The highest yield percentage of the obtained essential oils was 1.09% obtained by orange oil. The GC-MS analysis indicated that monoterpene and sesquiterpene hydrocarbons occupied the largest portion of the chemical composition of the three essential oils with D-limonene as the most predominant component. All essential oils showed activity against all tested organisms. Lime essential oil showed comparable antimicrobial activity relative to the commercial 78% alcohol hand sanitizer. In conclusion, essential oils obtained from citrus fruit peel represent a rich source of compounds possessing antimicrobial properties and could be an alternative to synthetic antimicrobial agents.